Josep Otón, an intellectual journey to give a reason for Christian hope - Vicente Algueró, Felipe J. de (Razón y fe, 2020)
Josep Otón is a prolific author, with some twenty books and numerous articles to his credit. His work can be framed within the sphere of Catholic intellectuals because of his vocation to build bridges that encourage dialogue between the Christian faith and contemporary thought. Specialized in the study of the French philosopher Simone Weil, he has written extensively on mysticism, interiority and biblical spirituality. As a multifaceted writer he has also devoted himself to narrative. As a whole, his thought is in keeping with the method of immanence proposed by Maurice Blondel.